1997
DOI: 10.1002/(sici)1097-0274(199702)31:2<188::aid-ajim8>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Lead levels in Maryland construction workers

Abstract: A cross‐sectional study of unionized construction workers not currently known to be performing lead work was conducted. Participants completed an interviewer‐administered questionnaire obtaining information about demographics, work history, other possible sources of lead exposure and health status (including hypertension, noise‐induced hearing loss and renal disease). Blood was then obtained via venipuncture for whole blood lead level, hematocrit and free erythrocyte protoporphyrin determination. Two hundred a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 21 publications
(23 reference statements)
0
12
0
Order By: Relevance
“…Accordingly, the study demonstrated the contribution of both endothelial and vascular smooth muscle cells to the pathogenesis of lead-induced oxidative stress in the vascular tissues. In addition to causing HTN, chronic exposure to lead results in a marked increase in the development of arteriosclerotic cardiovascular disease [1,19]. Oxidative stress plays a central role in the pathogenesis of atheroand arteriosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the study demonstrated the contribution of both endothelial and vascular smooth muscle cells to the pathogenesis of lead-induced oxidative stress in the vascular tissues. In addition to causing HTN, chronic exposure to lead results in a marked increase in the development of arteriosclerotic cardiovascular disease [1,19]. Oxidative stress plays a central role in the pathogenesis of atheroand arteriosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a number of clinical and epidemiologic studies have uncovered a convincing link between occupational lead exposure, HTN, and cardiovascular disease [11][12][13]. The observation that chronic lead exposure causes HTN in both experimental animals and occupationally exposed humans, and that the incidence of HTN is high within industrial societies characterized by widespread environmental lead contamination lends support to the belief that environmental lead exposure may contribute to the pathogenesis of the so-called essential HTN in the general population.…”
Section: Epidemiologic Considerationsmentioning
confidence: 99%
“…6 6 The 31 studies listed in Table 1 included 48 different groups of subjects. Of these groups, 32 consisted only of men or almost exclusively of men (99%), 75 15 only of women, and one 55 comprised both men and women. The combined estimates involved 58 518 subjects for systolic blood pressure and 58 491 subjects for diastolic blood pressure.…”
Section: Journal Of Human Hypertensionmentioning
confidence: 99%